Effect of Filler on Shear Strength and Electrical Conductivity in Epoxy Based Aluminium Bonded - Cahyo Yuniwantoro; Eko Surojo; Dharu Feby Smaradhana; Fitrian Imaduddin (Universitas Sebelas Maret, 2020)
Adhesive joint is one of the material joining techniques using a low temperature with the help of polymer adhesives to connect a material. This connection is widely used in infrastructure, automotive and electronics industries. This research was conducted to determine the effect of filler on shear strength and electrical conductivity on epoxy-based aluminum connections. The fillers used were aluminum powder, iron powder, copper powder with a grain size of 0.071 mm each and nanogold particles in liquid form. The connection type used is a single lap joint with an end tab modification at the end of the connection. The highest shear strength value is in the joint without the addition of filler of 3.17 MPa and the lowest value is in the connection with the addition of aluminum powder filler of 1.14 MPa. The highest value of electrical conductivity was obtained in epoxy mix with nanogold particle filler which was worth 13.1 S / m and the value for epoxy without the addition of filler was not detected because the resistance was too large. This shows that the addition of filler has an effect on the value of shear strength, which is to reduce the value of the shear strength, while for testing the conductivity of electricity the addition of filler has an effect to provide electric properties on epoxy.